Target leverage and speed of adjustment along the life cycle of European listed firms - Paula Castro; María Teresa Tascón Fernández; Borja Amor-Tapia; Alberto de Miguel (BRQ Business Research Quarterly, 2016)
This paper analyzes differences in target leverage and speed of adjustment across three life cycle stages of European listed firms: introduction, growth and maturity. We determine that profitability and tangibility are the most stable determinants, whereas growth opportunities and size exhibit changing effects across stages. The speed of adjustment does not increase as the firms evolve, as firms in introduction are able to adjust the fastest. Firms changing stage adjust leverage at a lower speed, and their target is more affected by profitability, primarily when the change is from growth to maturity. Finally, we confirm the existence of long-term debt targets, by providing evidence that the next-year target is a relevant factor to explain current debt when firms change from one stage to another."
Keywords: 650; Capital structure; Target leverage; Firm's life cycle; Speed of adjustment